The Relationship Between Knowledge Level and Anxiety Level in Patients with Chronic Kidney Failure in Gorontalo Provincial Hospitals - Firmawati, Firmawati; Retni, Ani; Zakaria, Mira Yunus (PROMOTOR, 2024)
Chronic kidney failure patients' knowledge of hemodialysis can affect a person's psychological condition. A patient's lack of knowledge about hemodialysis can cause anxiety. This anxiety will have an impact on the psychological threat to the patient, if it occurs continuously, it will cause the patient's psychiatric disorders or other diseases such as the heart. The purpose of this study is to determine the relationship between the level of knowledge and the level of anxiety of chronic kidney failure patients in hospitals in Gorontalo Province. The design of the analytical survey research with a cross-sectional study approach, the population of chronic kidney failure patients who underwent hemodialysis was 48 people at Prof. Dr. H. Aloei Saboe Hospital and Toto Kabila Hospital, the number of samples was 48 people using the total sampling technique and the statistical test used, namely chi-square. The results of the study were obtained from patients with good knowledge who experienced mild anxiety in as many as 12 people and moderate anxiety in as many as 3 people. Meanwhile, patients with sufficient knowledge experienced mild anxiety in as many as 4 people, moderate anxiety in as many as 8 people, and severe anxiety in as many as 3 people. In patients with less knowledge, 5 people experienced moderate anxiety and 13 people experienced severe anxiety. They were known as p-value=0.000<0.05. The conclusion is that there is a relationship between the level of knowledge and the level of anxiety in patients with chronic kidney failure in hospitals in Gorontalo Province.